Respuesta :

4+(-3)-2x(-6)=4-3+12=13

Answer: B.  13

Answer: B. 13

Step-by-step explanation:

The given expression : [tex]4 + (-3) - 2 \times (-6)[/tex]

Using PEDMAS → parenthesis , exponents , divide , multiply , add ,subtract.

Use these operation in order in the given expression.

[tex]4 + (-3) - 2 \times (-6)=4-3-2\times-6[/tex]  [(+)(-)=(-)]

[tex]=4-3+12[/tex]    [(-)(-)=(+)]

[tex]1+12=13[/tex]

Therefore, the answer to the given expression is 13.

hence, the correct answer is option B. 13.